2023
DOI: 10.29390/cjrt-2022-046
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of hypertonic saline versus isotonic saline among children with cystic fibrosis: A systematic review and meta-analysis

Abstract: Background Inhaled hypertonic saline (HS) reduces pulmonary exacerbations in patients with cystic fibrosis (CF) aged 6 or more years. However, the effectiveness of HS in improving clinical outcomes in younger children aged 6 or less years is not established. This study examines the efficacy of HS in younger CF patients. Methods Searches were conducted across three databases (Medline, Cochrane Central and EMBASE) from inception through July 2022. Randomized controlled tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…We have read with interest the study by Ullah et al [ 1 ], which found that inhaled hypertonic saline (HS) treatment significantly improves the lung clearance index (LCI), symptoms, lung function and quality of life in children affected by cystic fibrosis (CF) compared with isotonic saline (SI), which would support the use of this intervention in this population. These conclusions were reached by conducting a systematic review (SR), including seven clinical trials with 390 participants.…”
mentioning
confidence: 97%
See 3 more Smart Citations
“…We have read with interest the study by Ullah et al [ 1 ], which found that inhaled hypertonic saline (HS) treatment significantly improves the lung clearance index (LCI), symptoms, lung function and quality of life in children affected by cystic fibrosis (CF) compared with isotonic saline (SI), which would support the use of this intervention in this population. These conclusions were reached by conducting a systematic review (SR), including seven clinical trials with 390 participants.…”
mentioning
confidence: 97%
“…Disagreements were resolved by consensus. We used the data from the intervention effect estimation and the risk of bias (RoB) assessment from the studies reported by Ullah et al [ 1 ].…”
mentioning
confidence: 99%
See 2 more Smart Citations